A marketing plan for the Computerized Index to Philippine Periodical Articles (CIPPA) - Sagun, Karryl Kim A.
The Computerized Index to Philippine Periodicals Articles (CIPPA) is an in-house developed product by the Ateneo de Manila University Rizal Library. It was created primarily to serve the needs of the Ateneo community, as many have been clamoring for an easier way of locating publications by Filipinos, or about the Philippines, othewise known as Filipiniana materials. However, a number of local academic institutions have made requests to gain access to the index. This is comprised mostly of smaller institutional and academic libraries which cannot afford to create a database such as CIPPA on their own. After a few years of considering the idea, the Rizal Library opened the database for subscription to other interested parties. CIPPA's main market segments (outside of the Ateneo de Manila University) are comprised of local academic institutions : colleges, universities, and other research-intensive entities. They have been charged for a minimal fee, just enough to cover the maintenance expenses of delivering the service to them. The cost of creating and developing the product is shouldered fully by the Rizal Library.